Local Wisdom in the Customary Silent Burial System of the Baduy Community and Its Impact on Forest Conservation - Bagus Syarifuddin Latif; Kelvin Kelvin; Muhammad Izdihar Rasyiq Ramadhan; Adham Rizky Maulana; Alvina Soraya; Rais A Yudian (Ann Publisher, 2026)
Background. The Baduy indigenous community is one of the traditional communities in Indonesia that continues to preserve various forms of local wisdom in everyday life, including a customary burial system known as silent burial. This burial system is implemented based on customary law (pikukuh), which emphasizes simplicity, respect for nature, and a harmonious relationship between humans and the environment. Aim: This study aims to analyze the local wisdom embedded in the Baduy customary burial system and examine its contribution to forest conservation. Methods. This study employed a qualitative approach using ethnographic methods. Data were collected through observation, in-depth interviews, and a literature review. Results. The findings reveal that the silent burial practice is carried out without constructing permanent graves, using biodegradable natural materials and hanjuang plants as natural vegetation markers. This burial system facilitates natural land regeneration, minimizes landscape alteration, and supports the sustainability of forest ecosystems. Beyond its spiritual and social significance, the Baduy customary burial system also serves as a culture-based conservation mechanism that maintains long-term ecological balance. Conclusion. The findings demonstrate that the local wisdom of the Baduy indigenous community represents an effective model of environmental conservation integrated with traditional cultural values and offers valuable insights for the development of sustainable conservation practices.